Methane Production in Batch Anaerobic Digestion of Livestock Manures with Different Substrate Concentrations - Yodthongdee, Supawadee; Weerayutsil, Panomchai; Khuanmar, Kulyakorn (International Journal of Engineering and Technology, 2018)
This research aimed to evaluate the biochemical methane potential (BMP) of three livestock manures including swine manure (SM), chicken manure (CM), and dairy manure (DM) under the same conditions in batch anaerobic digestion (AD) including inoculum to substrate ratio, temperature, digestion time, concentration of total solids in the system, and reactor size.  The experiments were performed on individual manure, 2-manure mixture, and 3-manure mixture.  For the individual manure experiments, BMP of SM, CM, and DM were 326.97, 306.60, and 105.30 mL/gVSadded; and volatile solids (VS) removal values were 66.31, 62.47, and 52.02%, respectively. In the 2-manure mixture; SM: DM, SM: CM, and CM: DM ratios of 90:10%TS, the BMP were 278.15, 264.47, and 252.80 mL/gVSadded, respectively. In the 3-manure mixture, the maximum BMP was 200.82 mL/gVSadded under the SM: CM: DM combination of 74:20:6%TS. The conditions of the 3 experiments were similar: the total solids concentration at 20% of working volume and the temperature of 37°C. It could be concluded that each manure i.e., SM, CM, and DM could be used as raw material for methane production by anaerobic digestion. SM generated the highest BMP, followed by CM and DM, respectively.  However, DM should not be used as raw material alone, except combining it with SM or CM for better methane production.